Usia dan Paritas Ibu dengan Insidence dan Derajat Bayi Baru Lahir (BBLR) - Dwi Ertiana (EMBRIO: Jurnal Kebidanan, 2020)
Pregnancy aged <20 years and> 35 years with parity grandemulti can cause LBW. Age and parity are not the main causes of LBW, however LBW is influenced by many factors. Mothers who have high parity can experience disorders of the reproductive organs, especially in the uterus as well as disorders of the blood vessels. Therefore, someone should plan a pregnancy at a healthy reproductive age, namely the age of 20 - 35 years to reduce the possibility of problems during pregnancy. The research objective was to determine the relationship between maternal age and parity with insidence and degree of low birth weight in Kediri District Hospital. Correlational research design with cross sectional approach, using medical record data. Population 2399 using simple random sampling technique and paying attention to inclusion and exclusion criteria. Obtained a sample of 96, the sample was obtained by calculating the sample size formula Nursalam. Spearman rank statistical test with a value of ἀ 0.05. The result is that age at risk is 31.3%, parity at risk is 50%, while the degree of LBW is 20.8%. The results of the research analysis between age with insidence and degree of LBW (p value = 0,000 <0.05) r = 0.440), parity with insidence and degree of LBW (p value = 0.020 <0.05) r = 0.236. Age <20 years can cause LBW because pregnant women aged <20 years, the uterus and pelvis often have not yet maximized. Meanwhile, those aged> 35 years, there are changes in the reproductive organ tissue and the flexibility of the birth canal. Parity can cause LBW because high parity results in damage to the walls of the uterine blood vessels so that it interferes with the flow of nutrients to the fetus which causes LBW.